Pengembangan LKPD IPA Berbasis PBL (Problem Based Learning) Pada Materi Pencemaran Lingkungan SMP Kelas VII - Alex Kurniawan Almansyur; Agus Sujarwanta; Handoko Santoso (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The development of Science Student Worksheets (LKPD) based on Problem Based Learning (PBL) aims to produce teaching materials that are suitable for use in terms of content, language and design. Development is carried out using the ADDIE model, which includes the Analysis, Design, Development, Implementation and Evaluation stages. The LKPD product developed has been validated and is considered suitable for use in learning. This LKPD is expected to make the learning process more efficient, centered on students, and encourage them to find and solve problems with teacher guidance, thereby improving critical thinking skills through the PBL approach.